A study of learning, knowledge and processes of reflection within the worker education project - Abrahams_N, Nazli (School of Education, 2024)
There are over a million women domestic workers in South Africa who are largely overworked, underpaid, unprotected, and undervalued and who are entrenched in a system that denies and reduces the value of their work and their skills. Such conditions are invariably tied to contexts that are historically located. Domestic work is both necessary and valuable; however, in a context dominated by the structured social inequalities of race, class and gender, both their roles in society and their various skills and capacities are too often overlooked. Domestic workers have had to acquire a range of skills to effectively carry out the work they do and the learning involved is more often than not informal and tacit and the learning outcomes (skills, competencies, and knowledge) are not accredited or formally validated by society and institutions of education. The Worker Education Project, hosted by the South African Domestic Services and Allied Workers Union, which formed the context of the present study, was designed as an educational process in support of steps taken by domestic workers to organise themselves and develop and give expression to their own capacities to improve their living conditions. This study explores and tells the stories of women's lives as domestic workers and speaks of their experiences as women, as black women, and as domestic workers. To ground my analysis and my discussion, I provide an overview of the broad theoretical approaches that bear out the women's stories that turned on five sub-plots: learning, knowledge, alienation, their needs and desires, and the various relations of power that mediate their lives. In analyzing the said and done of the women, the very point is to attempt to understand how the women attach meaning to their lives. The research findings were drawn from semi-structured interviews, workshop facilitation and participation, and observations in situ. The results showed that the women learned from their experiences and through social participation in union activities, and that learning did not comprise only of hard skills, but that the women learned about themselves through processes of reflection. The research also revealed power as a prevailing condition (both complex and at times contradictory) central to all of the women's stories, operating in all spheres of their lives. This study attempts to open a political space for change and would like to suggest that learning is no less learning when the actors are domestic workers.